In vitro-evaluation of secondary caries formation around restoration. - Okida, Ricardo Coelho [UNESP]; Mandarino, Fernando; Sundfeld, Renato Herman [UNESP]; de Alexandre, Rodrigo Sversut; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (Tokyo Dental College, 2008)
The objective of this in vitro study was to evaluate demineralization around restorations. Class V preparations were made on the buccal and lingual surfaces of each tooth. TPH (Group 1), Fuji II LC (Group 2), Tetric (Group 3), Dyract (Group 4), GS 80 (Group 5) and Chelon Fil (Group 6) were randomly placed in equal numbers of teeth. The teeth were submitted to a pH-cycling model associated with a thermocycling model. Sections were made and the specimens were examined for the presence of demineralization under polarized light microscopy. Demineralization was significantly reduced with Chelon Fil (Group 6). Furthermore, a similar inhibitory effect on the development of demineralization was observed in Groups 2, 4 and 5.
Keywords: anticaries agent; compomer; dental alloy; fluoride; glass ionomer; resin; chemistry; comparative study; dental care; dental surgery; endodontics; human; methodology; polarization microscopy; recurrent disease; tooth disease; Cariostatic Agents; Compomers; Composite Resins; Dental Amalgam; Dental Leakage; Dental Restoration, Permanent; Fluorides; Glass Ionomer Cements; Humans; Marginal Adaptation (Dentistry); Microscopy, Polarization; Recurrence; Tooth Demineralization; Tooth Remineralization